Time-resolved fluorescence immunoassay for urine retinol-binding protein is more sensitive than polyclonal and monoclonal assays. (September 2021) - Salota, Rashim; Lapsley, Marta; Nabi, Ekramun; Packer, Simon; Hyer, Steve; Dockrell, Mark
Background: Retinol-binding protein4 (RBP) assays using polyclonal antibodies (pRBP) have major problems of non-linearity of dilution and a very small useable dynamic range. Our objective was to develop a specific assay with a wider dynamic range to detect tubular proteinuria. Methods: mRBP (monoclonal capture and second antibody with colorimetric detection) and fluoroimmunoassays for RBP (fRBP) (polyclonal capture and monoclonal second antibody with fluorescence detection) were developed and compared with pRBP. Four hundred and eighty-eight patient samples were collected; 290 samples were analysed by mRBP and 198 samples with fRBP and compared with pRBP. Results: mRBP assay has the advantages of better linearity on dilution and wider analytical range over pRBP. It is limited by poor signal in the patients with albuminuria and glomerular proteinuria and inferior discrimination between patient groups. fRBP had an intra-assay and inter-assay CV of <6% and <8%, respectively, and analytical range was 2.3–599 µ g/L. fRBP was linear on dilution within the analytical range. Correlation (r) was 0.8722 (95% CI 0.7621 to 0.9333, P < 0.0001); Mann-Whitney test revealed no significant difference (U = 18, 877, n = 198, P = 0.5244) asserting that the medians of the two samples were identical. Bland-Altman test between pRBP and fRBP showed a mean negative bias of 16.43 (CI –994 to 1027) µ g/mmol. Conclusions: The combination assay with fluorescence detection (fRBP) proved more discriminatory than a purely monoclonal system especially in patients with significant proteinuria and has advantages of better linearity on dilution and wider analytical range than the existing pRBP assay and compared extremely well with pRBP.